THREE SONNETS BY ADAM MICKIEWICZ: TRANSLATIONS AND COMMENTARIES - Paiva de Souza, Marcelo (Revista de Letras, 2023)
In this article, I present and briefly discuss my translations of three sonnets by Adam Mickiewicz, published in the collection Sonety, in 1826: “Stepy akermańskie” (The steppes of Akkerman), “Dobranoc” (Good night) and “Dzieńdobry” (Good morning), the first belonging to the cycle “Sonety krymskie” (Crimean Sonnets) and the remaining two, to the “Sonety erotyczne” (Erotic Sonnets) – also called “Sonety odeskie” (Odessa Sonnets). I begin by locating the texts in the coordinates of Mickiewicz's life and work, and then focus on two basic points: the factors that determined the choice of the translated poems and the assumptions and general parameters that guided the translation work. Then, I focus on each of the sonnets, to comment on the most relevant aspects of their respective translation. I make reference throughout my text to historians of Polish literature (Czesław Miłosz and Dorota Siwicka), to specialists in Mickiewicz’s poetry (Henryk Siewierski, Maria Dłuska, Zbigniew Majchrowski, among others), as well as to translation theorists and scholars (especially Efim Etkind). Keywords: Sonety (Sonnets), by Adam Mickiewicz; Polish Romanticism; Translation Studies.